Analysis of Appropriations for Recurrent and Capital Costs to Federal Universities in Nigeria, 2016 - 2022 - ICHA, Boniface Ijuo (Ilorin Journal of Education, 2024)
This study analyzes the appropriations for personnel, overhead, and capital costs to federal universities in Nigeria from 2016 - 2022. The study was conducted to analyse the proportions of total budgetary allocations that were allotted for personnel, overhead, and capital costs to federal universities and the impact on staff welfare and manpower development. The extent of funding the staff welfare and capital projects in federal universities certainly are the determinant of staff contentment and provision of quality facilities for quality assurance. The study adopted ex-post facto research design. The population of this study was the fifty (50) federal universities in Nigeria. The entire population was used for the study, hence there was no sampling. Proforma was used to collect certified data on records of annual appropriations for personnel, overhead, and capital costs to federal universities in Nigeria during period under study. Percentage and meta-analysis were employed in data analysis and the results presented in tables and charts. The study established that 91.91%, 1.70% and 6.39%, were appropriated for personnel, overhead, and capital costs, respectively. This implies that approximately 94% of federal universities budgetary allocations was appropriated for consumption at the expenses of capital costs with its attendant consequences on infrastructural facilities for quality manpower development. Therefore, the Federal Government is urged to step-up the annual appropriations for capital costs for improved universities facilities, which has direct bearing on quality of instruction.